2020
DOI: 10.2147/rmhp.s277464
|View full text |Cite
|
Sign up to set email alerts
|

<p>Obstetric Telephone Triage</p>

Abstract: Objective Little is known about obstetric telephone triage: the methods used to prioritize the severity of symptoms of obstetric emergency and other unplanned care requests originating by telephone. In large-scale obstetric units, there is a need for an evidence-based triage guideline. The aim of this study was to develop an obstetric guideline for telephonic triage. Design, Setting and Participants A multi-phase multi-center study was performed with consecutive drafts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…16,17 Current evidence suggests that the use of a multivariate approach with external validation can be seen as the highest achievable goal. 4,5,17 The results of this study, which was conducted in line with this approach, as well as (earlier) confirmation of DOTTS content validity 22 support this conclusion. Nevertheless, we need to stay critical about whether triage can be compared to screening tool studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…16,17 Current evidence suggests that the use of a multivariate approach with external validation can be seen as the highest achievable goal. 4,5,17 The results of this study, which was conducted in line with this approach, as well as (earlier) confirmation of DOTTS content validity 22 support this conclusion. Nevertheless, we need to stay critical about whether triage can be compared to screening tool studies.…”
Section: Discussionsupporting
confidence: 82%
“…Staff is given the opportunity to overrule the DOTTS urgency category. 22 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch Obstetric Telephone Triage System (DOTTS) aims to provide a uniform and practical triage system, and was developed through a multi-phase multi-center study in consultation with all stakeholders. 18 DOTTS is an evidence-based triage system, which uses presenting symptoms to classify the level of urgency. Recently published research into validity of DOTTS showed an acceptable diagnostic validity with room for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…19 DOTTS was introduced in 2015 and is currently used in 26% of all Dutch hospitals (n=20/78). 18,20 The purpose of this study is to determine the reliability of DOTTS.…”
Section: Introductionmentioning
confidence: 99%